Agronomic Performance and Stability of Kabuli-type Chickpea (Cicer arietinum) Genotypes in Northwestern Ethiopia - Adebabay, Anteneh; Haiu, Abebe; Ayana, Muluken; Sendekie, Fentaneshi; Amare, Aragaw; Kefale, Yohannes; Biset, Fentahun; Azanw, Melaku; Kindie, Mulatie; Fentahun, Birihanu (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Chickpea (Cicer arietinum) is a versatile pulse crop commonly grown in Ethiopia. The study aimed to develop a stable, high-yielding Kabuli chickpea variety with broad adaptability. The research was conducted over three years across eleven environments, testing thirteen genotypes using a randomized complete block design with three replications. GGE biplot analysis and a multi-trait stability index (MTSI) were used to identify genotypes that are both high-yielding and stable. The combined ANOVA showed significant differences among the genotypes for all traits except seed per pod (SPP). The highest grain yield, 1897.7 kg/ha, was recorded for genotype DZ-2012-CK-0291 (G12), followed by DZ-2012-CK-0306 (G13) with 1797.2 kg/ha. The lowest yield was observed in the variety Acosdubie, with 1023.3 kg/ha. Stability analysis comparing mean performance and stability indicated that genotypes DZ-2012-CK-0291 (G12) and ICCI449XEjerip6-14 (G1) were both high-yielding and stable. Conversely, Acosdubie (G4), Flip-09-76c (G6), and Arerti (G10) were stable but low-yielding. Meanwhile, DZ-2012-CK-0025 (G7), Flip-09-187c (G8), and DZ-2012-CK-0306 (G13) were high-yielding but unstable across environments. The results from the MTSI showed that DZ-2012-CK-0291 (G12) and Flip-93-146-c (G11) were stable across different environments. In conclusion, DZ-2012-CK-0291 (G12) proved to be the most suitable chickpea variety for cultivation in northwestern Ethiopia, based on both yield and stability.